2001
DOI: 10.1007/s004280100540
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the multi-step progression of mixed glandular–neuroendocrine gastric carcinomas

Abstract: A mixed glandular-neuroendocrine gastric carcinoma shows discrete, juxtaposed areas of adenocarcinoma and neuroendocrine carcinoma. In order to gain insight into the genetic events and clonality associated with the dual differentiation of a mixed gastric carcinoma, eight cases (two true composite and six neuroendocrine-dominant carcinomas) were examined by analyzing the genome-wide loss of heterozygosity (LOH). Of the eight mixed gastric carcinomas, one true composite and five neuroendocrine-dominant carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
69
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 28 publications
5
69
1
Order By: Relevance
“…In agreement with this model, two different studies have recently reported a microallelotyping analysis of seven colorectal PDECs (Vortmeyer et al, 1997) and of eight gastric PDECs (Kim et al, 2002) associated with adenomas or adenocarcinomas. In both studies, using a genomewide approach (Kim et al, 2002) or a loss of heterozygosity (LOH) analysis restricted to APC, DCC, and p53 loci (Vortmeyer et al, 1997), a close genetic relation-ship was observed between the two components, regardless of the typology of the mixed tumors analyzed. Because additional genetic alterations restricted to PDEC have been detected, it was speculated that a mixed exocrine-endocrine tumor evolves from a single epithelial precursor following an exocrine to endocrine cell-type sequence and not vice versa (Kim et al, 2002).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…In agreement with this model, two different studies have recently reported a microallelotyping analysis of seven colorectal PDECs (Vortmeyer et al, 1997) and of eight gastric PDECs (Kim et al, 2002) associated with adenomas or adenocarcinomas. In both studies, using a genomewide approach (Kim et al, 2002) or a loss of heterozygosity (LOH) analysis restricted to APC, DCC, and p53 loci (Vortmeyer et al, 1997), a close genetic relation-ship was observed between the two components, regardless of the typology of the mixed tumors analyzed. Because additional genetic alterations restricted to PDEC have been detected, it was speculated that a mixed exocrine-endocrine tumor evolves from a single epithelial precursor following an exocrine to endocrine cell-type sequence and not vice versa (Kim et al, 2002).…”
supporting
confidence: 54%
“…Therefore, it is not clear if the biphenotypic differentiation represents a genetic continuum from a common pluripotent stem cell or if the exocrine and endocrine tumor components arise from two distinct precursors through different tumorigenetic pathways (Kim et al, 2002;Peison and Benisch, 1983;Vortmeyer et al, 1997;Yamashita and Flinner, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,38 Nonetheless, recent reports of frequent 18q LOH in midgut carcinoids indicate that a novel putative tumor suppressor gene (distinct from DCC or DPC4) that is located on 18q may play an important role in the pathogenesis of midgut endocrine tumors. 15,16 In an attempt to evaluate whether the pathogenesis of PDECs is more consistent with that of WDECs, as suggested by some studies, [5][6][7][8] or with that of classical nonendocrine adenocarcinomas (i.e., CRCs), as suggested by other reports, 3,4 we compared the gastric subset of PDECs with a series of gastric WDECs and also compared the colorectal subset of PDECs with a series of CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PDECs and nonendocrine carcinomas originate from a common multipotent stem cell. 3,4 In contrast, another study, on mixed glandular-neuroendocrine carcinomas, found different genetic alterations in the two tumor components. 5 Furthermore, some studies on gastric PDECs have revealed extensive allelic deletions in the region containing the MEN1 gene that are responsible for multiple endocrine neoplasia type 1 syndrome.…”
mentioning
confidence: 93%